Genetic Variability Studies in Fennel (Foeniculum vulgare) in Arid Western Rajasthan - Jat, Mahipal; Choudhary, Santosh (Annals of Arid Zone, 2022)
Eighteen genotypes of fennel were evaluated to assess the extent of genetic variability, heritability, and genetic advance. Analysis of variance showed significant differences among the genotypes and significant variability concerning all the characters. Phenotypic variances estimates were higher than genotypic variances for all the characters, but the difference was low, depicting lower influence of environment on the expression of the traits. In addition, high heritability (broad sense) coupled with high genetic advance as a percent of mean was observed in fennel genotypes for dry matter accumulation at maturity, biological yield, harvest index (%), and oil content. The genotype RF-205 performed prominent for seed yield and essential oil content which is the important economical trait, this genotype is an important genetic resource for fennel genetic improvement for arid environment.